Konsep Monotheisme dalam Islam: Analisis Teologis tentang Tauhid - A.Nirwana Humairah A Nur; Ilmi Pratiwi Rasyid; St Mutiah Nurul Ilmidarajatih; Wildan Hidayat; Abbas Baco Miro; Ahmad Nashir (CV. ITTC INDONESIA, 2026)
This study explores the concept of Tawhid in Islam, which affirms the oneness of Allah SWT and serves as the foundation for Islamic thought, ethics, and practice. The study examines the three main dimensions of Tawhid : rubūbiyyah, ulūhiyyah, and asmā’ wa ṣifāt, and their implications for human relationships with God, fellow humans, and the universe. It highlights the importance of Tawhid in shaping a worldview responsive to modern social and moral issues. The research method includes phenomenological study, library research, and content analysis of classical and modern Islamic theological texts. The findings emphasize that Tawhid must be internalized in both mindset and social actions, impacting spiritual, social, and ecological life. Tawhid fosters dependence on Allah, promotes social equality and justice, and encourages ecological responsibility as guardians of nature. The study suggests that understanding Tawhid is essential for developing a contextual and responsive curriculum for Islamic faith education in the contemporary world.